Free school meals and educational outcomes: evidence from China’s Nutrition Improvement Program - Ma, Zhanli; Ma, Yanna; Zou, Wei; Fan, Zengzeng (Frontiers in Public Health, 2025)
The education gap between urban and rural areas has long been a significant challenge for developing countries. This study evaluates the impact of China’s large-scale Nutrition Improvement Program (NIP) on the educational outcomes of rural children, investigating the root causes of the urban–rural education divide from the early stages of human capital development. Using data from the China Family Panel Studies (2010–2020), we reveal three notable findings: (1) NIP has significantly boosted rural children’s language grades by 0.223 standard deviations and math grades by 0.172 standard deviations. Over the long term, NIP raised the high school enrollment rate by 8.2%. (2) Heterogeneity analysis indicates that NIP is more effective for relatively disadvantaged groups, such as girls, younger children, and children from low-income families. (3) NIP enhances children’s educational outcomes by improving children’s nutritional intake, strengthening cognitive and non-cognitive abilities, reshaping family educational expectations, and increasing families’ investment in education. Our findings provide valuable insights for refining public policies and contribute significantly to advancing educational equity across regions.